Reflection on the Identity of the Outermost Indonesian Community on Sebatik Island through Malaysian Television Broadcasts - Rizki Briandana; Rustono Farady Marta; Azman Azwan Azmawati (Fakultas Ilmu Komunikasi Universitas Tarumanagara, 2021)
This study aims to analyze the interpretation of Indonesian people in Sebatik Island towards Malaysian television programs. The Sebatik community is a marginalized community who does not have access to Indonesian television broadcasts. To get Indonesian television broadcasts, they have to buy satellite dishes which the majority of the people of Sebatik Island cannot afford. But on the other hand there is a leak of Malaysian television broadcasts in the Sebatik Island area. In this case, they rely on Malaysian television broadcasts which are very accessible at all times. This situation continued for many years and Malaysian television broadcasts became the main source of communication media. This study uses the theory of Interpretive Communities, Stanley Fish. The methodology used in this study is reception analysis through focus group discussions, and observation as a data collection technique. Focus Group Discussion was conducted on the people of Sebatik Island who met the criteria in the study. The results showed that Malaysian television broadcasts were used as the main television broadcast of the Sebatik community in their daily lives. Malaysian television which contains the values and meanings of the Malaysian state is interpreted by the Indonesian people on the border of Sebatik Island. The interpretation results show that life in Malaysia is an ideal and perfect life for the people of Sebatik Island. Penelitian ini bertujuan untuk menganalisis interpretasi masyarakat Indonesia di Pulau Sebatik terhadap program televisi Malaysia. Masyarakat Sebatik adalah masyarakat terpinggir yang tidak memiliki akses siaran televisi Indonesia. Untuk mendapatkan siaran televisi Indonesia, mereka harus membeli parabola yang harganya tidak mampu dibayar oleh mayoritas masyarakat Pulau Sebatik. Namun disisi lain terdapat kebocoran siaran televisi Malaysia di kawasan Pulau Sebatik. Dalam hal ini, mereka mengandalkan siaran televisi Malaysia yang sangat mudah diakses setiap saat. Situasi ini berlangsung selama bertahun-tahun dan siaran televisi Malaysia menjadi sumber utama media komunikasi. Penelitian ini menggunakan teori Interpretive Communities, Stanley Fish. Metodologi yang digunakan dalam penelitian ini adalah analisis resepsi melalui focus group discussion, dan observasi sebagai teknik pengumpulan data. Focus Group Discussion dilakukan terhadap masyarakat Pulau Sebatik yang memenuhi kriteria dalam penelitian. Hasil penelitian menunjukkan bahwa siaran televisi Malaysia digunakan sebagai siaran televisi utama komunitas Sebatik dalam kesehariannya. Televisi Malaysia yang bermuatan nilai dan makna negara Malaysia di interpretasi oleh masyarakat Indonesia di perbatasan Pulau Sebatik. Hasil interpretasi menunjukan, kehidupan yang ada di Malaysia merupakan kehidupan yang ideal dan sempurna bagi masyarakat Pulau Sebatik.